Emisi gas rumah kaca (CO2 dan CH4) pada kawasan mangrove di Pesisir Desa Poka, Kota Ambon - Rahman, Rahman; Kesaulya, Irma; Ikbal, La (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
The organic material input that enters the waters of Ambon Bay spreads to the mangrove ecosystem area and is partially deposited in sediments, including the mangrove area of ​​Poka Village. This study aims to analyze greenhouse gas emissions (CO2 and CH4) in mangrove sediments in the Poka Village area. The gas collection was carried out using a cylindrical cap method placed on three types of sediment, namely sandy silt (LPs), muddy sand (PsL), and sand (Ps). Gas concentration analysis refers to the gas chromatography method. The results showed that the largest CO2 emissions were found in LPs sediments, 138.94 mg/m2/hour. Meanwhile, the lowest emission was found in PsL sediment, which was 20.69 mg/m2/hour. In addition, the largest CH4 emission was also found in the LPs sediment type, 0.2154 mg/m2/hour. Meanwhile, the lowest CH4 emission was found in the Ps sediment type, 0.0447 mg/m2/hour. Greenhouse gas emissions (CO2 and CH4) in mangrove sediments on the Coast of Poka, Ambon Bay, are still relatively low compared to Indonesia's average emissions from other mangrove ecosystems. The sandy-mud sediment type has greater emissions than the silty-sand and sand sediment types which are influenced by the availability of total organic carbon in each mangrove sediment.